STRATEGI ADAPTASI TUKANG BECAK DALAM KEHIDUPAN SOSIAL EKONOMI (Studi Kasus Tukang Becak di Kelurahan Bontobiraeng Kecamatan Mamajang Kota Makassar) - Mangatta, Baihaqi Hendri (HOLISTIK, Journal Of Social and Culture, 2016)
Some of them are still can found a means traditional transportation of Becak in several regions of general and especially the Makassar City. For the past few years little by little the number of Becak began to unravel, because literally irreplaceable with a vehicle which is much more modern and fast. Becak drivers is a livelihoods just have to rely on physical force. Paddling are is not a matter easy and is done daily from morning to afternoon sometimes into the evening. But, they realized just a job this is what they can do to support their families. Fulfill their needs is felt difficult by a few people if what they produced from his job not in accordance with the need to be. Therefore they must be able to prioritise what has been need or just a desire. The becak drivers only a few comes from the town of Makassar most are from regional the province of south sulawesi, as Jeneponto, Gowa, Maros, Pangkep, etc. One of the reasons they work as becak drivers is because apart from people interested transportations service of becak there are still, the job is also one of the that does not require the level of education high or did not even need to seek the education formal. Keywords: becak, transportation, informal.